Personal and entrepreneurial characteristics of nascent and active entrepreneurs: GUESSS Colombia study [Características personales y empresariales de emprendedores nacientes y activos: Estudio GUESSS Colombia] (2018)
This article identifies the main characteristics of nascent and active entrepreneurs. We use the information from the GUESSS Colombia 2013/2014 study. Main findings show that the rate of nascent and active entrepreneurs in Colombia is higher than worldwide and that the main industry sector of planned and existing firms are trade and ICT industries. Likewise, nascent entrepreneurs start up their firms with partners, while active entrepreneurs contribute with the majority of the equity, considering that they perform better than competitors and are optimistic with the growth of their firms. © 2018.Este artículo identifica las características de los emprendedores nacientes y activos. Se utiliza la información del estudio GUESSS Colombia 2013/2014, señalando que la tasa de emprendedores nacientes y activos es mayor que a nivel mundial, y que los principales sectores industriales para el emprendimiento son el comercial y el de TIC. Igualmente, los emprendedores nacientes inician sus empresas con socios, mientras que los emprendedores activos aportan la mayoría del capital de sus empresas, considerando que se desempeñan mejor que sus competidores y son optimistas con el crecimiento de sus firmas. © 2018.